1973
DOI: 10.1507/endocrj1954.20.175
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation by Progesterone of Ovulating Hormone Release in Sodium Pentobarbital-Blocked Proestrous Rats

Abstract: SynopsisIn order to elucidate the facilitatory action of progesterone on the CNS mechanism(s) regulating ovulating hormone (OH) release, the steroid (5mg/rat) dissolved in sesame oil was injected subcutaneously to proestrous rats which had been treated with the minimal dose of sodium pentobarbital (PB, 25 or 22.5mg/kg, ip) to inhibit spontaneous OH release. Low (20-30%) incidence of ovulation (No. of rats ovulated against No. of rats treated) was obtained on the following day in the rats given PB alone. When p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Specifi¬ cally, progesterone administered on dioestrus is known to delay the genesis of that phenomenon by 24-48 h (Zeilmaker, 1966;Kobayashi, Hara & Miyake, 1969a;Caligaris, Astrada & Taleisnik, 1971; Beattie & Corbin, 1975;Taya, Terranova & Greenwald, 1981), while progesterone administration on the morning of pro-oestrus will advance the timing of the onset of the LH surge by a few hours (BrownGrant & Naftolin, 1972;Kobayashi, Hara & Miyake, 1973;Kalra & McCann, 1974;DePaolo & Barraclough, 1979a;Barraclough, Camp, Wieland & Akabori, 1986). In addition, in the ovariectomized, oestradiol-primed rat model, progesterone also markedly augments LH surge amplitude (Aiyer, Sood & Brown-Grant, 1976;DePaolo & Barraclough, 19796;Wise, Grossman & Barraclough, 1981a).…”
mentioning
confidence: 99%
“…Specifi¬ cally, progesterone administered on dioestrus is known to delay the genesis of that phenomenon by 24-48 h (Zeilmaker, 1966;Kobayashi, Hara & Miyake, 1969a;Caligaris, Astrada & Taleisnik, 1971; Beattie & Corbin, 1975;Taya, Terranova & Greenwald, 1981), while progesterone administration on the morning of pro-oestrus will advance the timing of the onset of the LH surge by a few hours (BrownGrant & Naftolin, 1972;Kobayashi, Hara & Miyake, 1973;Kalra & McCann, 1974;DePaolo & Barraclough, 1979a;Barraclough, Camp, Wieland & Akabori, 1986). In addition, in the ovariectomized, oestradiol-primed rat model, progesterone also markedly augments LH surge amplitude (Aiyer, Sood & Brown-Grant, 1976;DePaolo & Barraclough, 19796;Wise, Grossman & Barraclough, 1981a).…”
mentioning
confidence: 99%
“…Brown-Grant (1969) has suggested that the pre-ovulatory release of pro¬ gesterone may act as a ' fail-safe ' mechanism in stimulating LH release via a positive feedback mechanism. Recently Kobayashi, Hara & Miyake (1973) have shown that in pro-oestrous rats treated with sodium pentobarbitone, progesterone administered after the critical period significantly increases the incidence of ovulation.…”
Section: Discussionmentioning
confidence: 99%